Calculation and Control Methods for Equivalent Resilient Modulus of Subgrade Based on Nonuniform Distribution of Stress. (8th September 2019) - Yao, Yongsheng; Qian, Junfeng; Li, Jue; Zhang, Anshun; Peng, Junhui
Abstract : The resilient modulus of subgrade is a design parameter of the pavement structure, which is significantly affected by the overlying load and traffic load. It is important to calculate the equivalent resilient modulus of the top surface of subgrade based on the nonuniform distribution of resilient modulus in subgrade. This paper takes the fully weathered granite soil as the research object. Firstly, the soil density of different layers of the subgrade structure is calculated by the degree of compaction of different subgrade layers. Secondly, the overlying load of each point in the subgrade is determined based on the quality of subgrade. Thirdly, the subprogram of the finite element software is compiled and redeveloped based on the elastic constitutive model, and the calculation method for the resilient modulus of each point in the subgrade under the traffic load is proposed when the convergence criterion is set up. Finally, according to the deflection equivalence of the elastic double layer and elastic half-space, the calculation and control methods for equivalent resilient modulus of the top surface of subgrade under nonuniform stress distribution are put forward, and the field verification tests are carried out. The results show that the error range between numerical calculation and field measurement of equivalent resilient modulus of subgrade is 10%. It shows that the calculation method for equivalent resilient modulus of subgrade proposed in this study is reasonable and effective. The equivalent resilient modulus of subgrade decreases with the increase of traffic load. And the resilient modulus of subgrade soil increases with the increase of subgrade depth. The resilient modulus of subgrade soil has a significant impact on the equivalent resilient modulus of subgrade after the overlaying gravel layer. The equivalent resilient modulus of the subgrade with the gravel layer increases with the increase of the resilient modulus of the subgrade soil.